Updates in Volcanology From Volcano Modelling to Volcano Geology - Nemeth, Karoly (IntechOpen, 2016)
Updates in Volcanology - From Volcano Modeling to Volcano Geology is a new book that is based on book chapters offered by various authors to provide a snapshot of current trends in volcanological researches. Following a short Introduction, the book consists of three sections, namely, ''Understanding the Volcano System from Petrology, Geophysics to Large Scale Experiments,'' ''Volcanic Eruptions and Their Impact to the Environment,' and ''Volcanism in the Geological Record.'' These sections collect a total of 13 book chapters demonstrating clearly the research activity in volcanology from geophysical aspects of volcanic systems to their geological framework. Each chapter provides a comprehensive summary of their subject's current research directions. This book hence can equally be useful for students and researchers.